2021
DOI: 10.5702/massspectrometry.a0094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dimensionality Reduction Methods in Mass Spectra of Astrocytoma and Glioblastoma Tissues

Abstract: Recently developed methods of ambient ionization allow the collection of mass spectrometric datasets for biological and medical applications at an unprecedented pace. One of the areas that could employ such analysis is neurosurgery. The fast in situ identification of dissected tissues could assist the neurosurgery procedure. In this paper tumor tissues of astrocytoma and glioblastoma are compared. The vast majority of the data representation methods are hard to use, as the number of feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…One of the biggest challenges in clinical MSI concerns the validation of research outcomes due to the mismatch between the high number of dimensions as provided by omics technologies (“curse of dimensionality”) and the low number of samples. 29 In MSI, the number of detected ion signals defines the dimensionality and ranges from a few hundreds to several thousands. In contrast to this, the number of human samples for clinically motivated studies rarely surpasses 100 (not considering tissue microarray-based studies).…”
Section: Oncologymentioning
confidence: 99%
“…One of the biggest challenges in clinical MSI concerns the validation of research outcomes due to the mismatch between the high number of dimensions as provided by omics technologies (“curse of dimensionality”) and the low number of samples. 29 In MSI, the number of detected ion signals defines the dimensionality and ranges from a few hundreds to several thousands. In contrast to this, the number of human samples for clinically motivated studies rarely surpasses 100 (not considering tissue microarray-based studies).…”
Section: Oncologymentioning
confidence: 99%
“…It was shown that the molecular profiles of unmodified and damaged brain tissue are separable-various necrotized (necrotized tumor, necrotic tissue with necrotized vessels, necrotic tissue with tumor strain) and tumor (histologically pure tumor, tumor with necrosis, tumor lesions) tissues could be differentiated from each other as well as from the tumor boundary tissues [25]. The same data was further implemented to create classifiers for rapid identification of various tumors (glioblastoma, astrocytoma, meningioma) based on ambient mass spectrometry [34][35][36], which has become the basis for developing new ambient ionization techniques designed for clinical application [10]. On the other hand, the presented dataset, as it is an example of data representing actual data obtained in a clinic, was used as a model for developing an instrument for an interactive and automated tool for evaluating the stability and reproducibility of mass spectra [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], and for the unification of representations of high-and low-resolution mass spectra for further clinical implementation [23].…”
Section: User Notesmentioning
confidence: 99%
“…The same data was further implemented to create classifiers for rapid identification of various tumors (glioblastoma, astrocytoma, meningioma) based on ambient mass spectrometry [34][35][36], which has become the basis for developing new ambient ionization techniques designed for clinical application [10]. On the other hand, the presented dataset, as it is an example of data representing actual data obtained in a clinic, was used as a model for developing an instrument for an interactive and automated tool for evaluating the stability and reproducibility of mass spectra [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], and for the unification of representations of high-and low-resolution mass spectra for further clinical implementation [23].…”
Section: User Notesmentioning
confidence: 99%